How Did You Get Here? You’re Not Supposed to Be Here: Supporting the Social-Emotional and Mental Health Needs of Minoritized Twice Exceptional Students - Cormier, Christopher J. (Teaching exceptional children, 2025)
Teachers and other school officials must consider the ways in which they can support minoritized twice-exceptional (2e) students to address both their academic needs and their socioemotional needs. This article provides insights for supporting the socioemotional and mental health needs of minoritized 2e students. Fictionalized vignettes about Han and Lakeisha based on real-life experiences of minority 2e students are used to illuminate the daily lived school realities of minoritized 2e students. Suggestions for how teachers and schools can better support the mental well-being of this group of students are provided.